Remapping rational self: Rational emotive behavior therapy meningkatkan penyesuaian diri mahasiswa - Astinah, Astinah; Nur Widiasmara (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2023)
This study focuses on rational emotive behavior therapy (REBT) interventions for students who experience adjustment difficulties. The REBT approach is based on the concept that emotions and behavior result from cognitive processes. This study aims to measure the effectiveness of REBT in improving students’ self-adjustment abilities. This study used the single case expert design method with REBT treatment for 5th semester students who experienced adjustment problems. The data were analyzed descriptively by elaborating changes in students’ thoughts, feelings, and behavior before and after the REBT treatment. After receiving the REBT treatment, the student concerned showed an increase in self-adjustment, particularly in social adjustment, as shown by an increase in the self-adjustment score from 63 (low) to 102 (high). The subject experiences changes in thoughts, feelings, and behavior, such as the ability to accept that he is in trouble and not everything has to be according to his wishes. In addition, the subject is better able to change irrational beliefs to become rational so that they can achieve more stable emotions and adaptive behavior on campus. REBT is effective in increasing social adjustment in research subjects. Future researchers can use REBT by following the intervention steps in this study to be given to individuals who experience obstacles to social self-adjustment accompanied by irrational beliefs and unstable emotions.